Die soziale Selektivität des lebenslangen Lernens : diskontinuierliche Erwerbsverläufe als exkludierender Faktor - Schlenker, Annika [Verfasser] (My University, 2014)
"In the following work, we examine how exclusion affects the lifelong learning paths of adult learners, whose employment histories are often characterized by instability and discontinuity. The analysis of the three central facets often discussed in the literature of 'exclusion', allows for the ever increasing importance of the labour market in terms of structuring, and in the stabilization of 'exclusion risks' along with general education as an initial 'path' event. The results suggest the following conclusion: access to continuing education is often shaped by opportunity, and also individual demand. The attitude towards, or whether an individual engages in lifelong learning appears to be shaped early within a person. These early events of path dependency, as well as the identification of asymmetrical power relations as continuity assurance mechanisms, connected with the visible tendency to the exclusion of the self can be understood as a desideratum of reinforcement, which take into account the respective subject context relationship of (potential) participants in the educational program. If the concept of 'lifelong learning for all' is to become a reality, or is to be of any effect, several aspects appear to be necessary; namely, a broad, public sponsored vocational training, that focuses on the formation of the individual, coupled with sustainable, requisite skills, and knowledge base." (Authors' abstract)

"In der vorliegenden Arbeit wird analysiert, wie sich Pfade biografisch zunehmender Exklusion vom lebenslangen Lernen bei erwachsenen Lernern herausbilden, deren Erwerbsverläufe durch Instabilitäten und Diskontinuitäten gekennzeichnet sind. Die Analyse der drei in der einschlägigen Literatur diskutierten zentralen Vermittlungsinstanzen der Exklusion lässt neben dem allgemeinbildenden Schulabschluss als pfadinitiierendem Ereignis auch die zunehmende Bedeutung des Arbeitsmarkts im Hinblick auf die Strukturierung und Stabilisierung von Exklusionsrisiken sichtbar werden. Die frühzeitige Pfadinitiierung sowie die Identifikation asymmetrischer Machtverhältnisse als kontinuitätssichernde Mechanismen - verbunden mit der sichtbaren Tendenz zur Selbstexklusion - können als Desiderat einer verstärkten Berücksichtigung der jeweils vorliegenden Subjekt-Kontext-Relation der (potenziellen) Weiterbildungsteilnehmer verstanden werden. Wenn Konzepte lebenslangen Lernens breite inkludierende Wirkung entfalten sollen, erscheint öffentlich geförderte berufliche Weiterbildung notwendig, die sich verstärkt an der Formung der Person orientiert und nachhaltige, individuell als nützlich erfahrene Bildungsprozesse ermöglicht." (Autorenreferat, BIBB-Doku)
Keywords: G 2.2.4 Lebensbegleitendes & lebenslanges Lernen; S 1.5 Weiterbildung; G 2.4.1 Bildungs- und Berufswege; Lebenslanges Lernen; Weiterbildung; Berufsverlauf; Diskontinuität; Ausgrenzung; Bildungssystem; Beschäftigungssystem